Deleterious Interaction Between Honeybees (Apis mellifera) and its Microsporidian Intracellular Parasite Nosema ceranae Was Mitigated by Administrating Either Endogenous or Allochthonous Gut Microbiota Strains - El Khoury, Sarah; Rousseau, Andrée; Lecoeur, Alexandre; Cheaib, Bachar; Bouslama, Sidki; Mercier, Pierre-Luc; Demey, Vanessa; Castex, Mathieu; Giovenazzo, Pierre; Derome, Nicolas (Frontiers in Ecology and Evolution, 2018)
Honey bees (Apis mellifera) are facing multiple stressors affecting their lifespan, health and productivity. Among them, Nosema ceranae is an intracellular microsporidian parasite, which plays a major impact on honey bees colonies. However, both efficiency and innocuity of current treatment against N. ceranae are observed, thus raising the urgent need to develop alternative prophylactic and curative strategies. Endogenous microbial communities (i.e. host microbiota) are known to play a major role in disease prevention, and more recently both bacterial and yeast strains issued from gut microbiota were observed to improve hosts resistance against intracellular parasites both in mammals and insect models. The use of probiotics in honey bee nutrition is therefore promising to treat or prevent diseases. Therefore, further investigations are needed to properly select microorganisms with probiotic properties. In an in vivo experimental infection by Nosema ceranae, the probiotic effect of two honeybee gut bacterial strains (Parasaccharibacter apium (PC1 sp.) and (Bacillus sp. (PC2 sp.)), and two broad spectra probiotics (Bactocell® and Levucell SB®) has been measured. Both curative and prophylactic administrations were tested: honey bees infected with N. ceranae and non-infected. For the four probiotic candidates, significant increases of survival probabilities (20-30%) were measured after two weeks of treatment with the administration of 103 CFU/mL in sugar syrup, both in curative and prophylactic treatments. The present study shows that endogenous bacterial strains were at least as much efficient and safe than broad spectra probiotics in increasing survival in the context of experimental infection with N. ceranae. Therefore, taking advantage of beneficial host microbiota properties is a promising avenue to develop efficient and sustainable curative strategies against opportunistic diseases in honey bee colonies.